The Influence of Digital Marketing, Promotion and Prices on Online Purchase Decisions in the Era of the Covid-19 Pandemic - Evianah, Evianah; Mustikorini, Dwi Indah; Nuraini, Dewi (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine how much influence digital marketing, promotions and prices have on online purchasing decisions, using multiple linear regression statistical analysis tools. The results of the study show that simultaneously and partially digital marketing, promotion and price variables affect purchasing decisions almost at the @hampersurabaya store in the era of the covid-19 pandemic. In order to remain competitive in this pandemic era, @hampersurabaya must pay attention to pricing, convenience in online purchases, intensive promotions, and being sensitive to this pandemic condition, so that the products sold can be combined with health care products, which can later influence purchasing decisions. The results of observations made on respondents who work outside the home, who have a busy life in the office greatly affect them in making purchasing decisions, so the only way because of their busyness they end up having to make a lot of online purchasing decisions. Marketing through digital media has a huge impact on business people. With digital media, they can market their products widely, promotions carried out to attract many consumers can be easily obtained, for example by advertising their products through online promotions, by displaying their products through advertisements on Facebook, advertisements on Instagram and social media. other. This method is quite accurate, because currently Facebook and Instagram are still the most popular social media and almost all adults have Facebook and Instagram accounts. To find out the size of the price, consumers can easily get that information. Especially now that the world of marketing through the marketplace has mushroomed in almost all of the world.